The Relationship between Knowledge Level and Mother’s Readiness for Menopause - Ima Sukmawati; Aeli Yuliawati; Elis Noviati; Heni Marliany; Yuyun Rahayu; Rosmiati Rosmiati (LPPM STIKes Muhammadiyah Ciamis, 2023)
Introduction: Menopause is the permanent cessation of menstruation. Menopause is a normal life event, not a disease. This period is characterised by the cessation of menstruation as estrogen is not produced. This condition is a very ageing process in every woman. Women experiencing menopause need support from close people such as husbands, friends, and family. The readiness of mothers in facing menopause is influenced by several factors, such as education level, knowledge about menopause, socioeconomic factors that affect the body and health. Objective: To determine the relationship between knowledge and mothers' readiness to face menopause at Posyandu Sukasari Dahlia 2, Ciamis District. Method: This research is a study that uses quantitative methods, which wants to prove whether or not there is a relationship between the level of knowledge and the readiness of mothers in facing menopause at Posyandu Sukasari Dahlia 2, Ciamis District. The research was conducted in July 2023. This study included quantitative research using a cross-sectional analytic design. The population in this study were all mothers in Posyandu Sukasari Dahlia 2 Ciamis District. The population in this study amounted to 45 respondents, with total sampling technique. Result: The results showed that 40 respondents (88.9%) had sufficient knowledge, and the readiness of mothers to face menopause was 37 people (82.2%). Conclusion: Based on the research conducted, it can be concluded; the level of knowledge in the category is sufficient with a total of 40 respondents. Mother's readiness in facing menopause is categorised as ready, namely 37 respondents. There is no relationship between mother’s readiness in facing menopause at Posyandu Sukasari Dahlia 2 Ciamis District with a p value = 0.083 (p <0.05).